In conversation with Jennifer Walshe: performing with intelligent machines - Dyer, M; Kanga, Z; Walshe, J (Taylor & Francis, 2023)
In this interview, composer, performer and improviser Jennifer Walshe talks with Mark Dyer and Zubin Kanga about her work performing with machine learning algorithms and other intelligent machines. In contrast to the many articles and interviews that have largely focused on Walshe’s practice as a composer, this interview focuses on her practice as a performer integrating these technologies into her work, centring around ULTRACHUNK (2018) and IS IT COOL TO TRY HARD NOW? (2017). As well as discussing the effect machine learning technologies might have on the experimental music industry, Walshe reflects on the role of the performing human body in an era of technological proliferation.